An Upgradable Product Design Method for Improving Performance, CO2 Savings, and Production Cost Reduction: Vacuum Cleaner Case Study - Masato Inoue; Shuho Yamada; Tetsuo Yamada; Stefan Bracke (International Journal of Supply Chain Management, 2014)
Customers often discard products without considering the environmental load, because of the deterioration of their value even though they are fully functional. An upgradable product design can enhance the product value and stop the entire product replacement and disposal by replacing only the components responsible for the decrease in value. This paper proposes an upgradable product design method for improving product performance, incurring CO2 savings, and production cost reduction while increasing the product value and extending the value lifespan by exchanging components closely related to the deterioration in value. In addition, this paper proposes a method that can specify future product performance, effective upgradable product components, and the effect of the upgrade on other product components. Finally, this paper discusses the applicability of the proposed method by considering the designing of a vacuum cleaner and customer demands such as performance, noise, and energy savings.